CATALOGO DE TIPOS DE INSECTOS DEPOSITADOS EN LA COLECCION DEL INSTITUTO DE ENTOMOLOGIA-UMCE UNIVERSIDAD METROPOLITANA DE CIENCIAS DE LA EDUCACIÓN - Solervicens, Jaime; Henry, Abei (Acta Entomológica Chilena, 2022)
Insecl types (holotypes, allotypes, paratypes) deposited at the Collection oi ihe Inslituto de Entomología. l'mce, Santiago, are listed in this paper, reptesenting 999 lypes, corresponding to 144 laxa of 33 lamilies of Orders Odonata, Hemiptera, Coleóptera, Díptera, Lepidoptera and Hymenoplera. The insect fauna of the extreme north of the country (1 Región, Tarapaca) as well as l'rom the "Altiplano" in north Chile and the Archipelagoofjuan Fernández are particularly well represented in the Collection.